Think this, not that : 12 mindshifts to breakthrough limiting beliefs and become who you were born to be - Axe, Josh (Thomas Nelson Inc., 2024)
Are you feeling stuck? Wanting more out of life? Use twelve powerful mindshifts to break through limiting beliefs, spark personal transformation, and build a more meaningful life.